PENGEMBANGAN MEDIA SPINGAME BERBASIS POWERPOINT PADA PEMBELAJARAN IPA MATERI SUMBER ENERGI BAGI SISWA SEKOLAH DASAR - Windy Aprilia Magdalena Bety; Reza Syehma Bahtiar; Endang Nuryasana (Prima Magistra: Jurnal Ilmiah Kependidikan, 2022)
This study aims to determine the use of powerpoint-based spingame media for the even semester of the 2022/2023 academic year. The urgency of the background of this research is the lack of student learning materials in creating appropriate, practical, and effective learning. The aspect observed in the development of this media is the use of powerpoint-based spingame media in science learning material energy sources to increase student interest in learning for class V SDN Asemrowo II Surabaya. This type of research uses the ADDIE model development method with the steps of analysis, design, development, implementation, evaluation. The research subjects were students of V-A SDN Asemrowo II Surabaya. Data collection techniques in this study in the form of tests, questionnaires, interviews. Data were obtained and analyzed from learning outcomes test sheets, questionnaire sheets, and interviews. The results showed that the development of powerpoint-based spingame media could increase students' interest in learning as evidenced by the percentage of material experts by 97.5%, media experts by 92.5%, student responses with a percentage of 91.62%, and the results of the interviews were categorized as very good. Furthermore, the post-test showed an increase in student interest in learning compared to the pre-test by 60%.